UJI EFEKTIVITAS BEBERAPA KONSENTRASI BIOINSEKTISIDA Bacillus thuringiensis DALAM MENGENDALIKAN HAMA ULAT KANTONG (Metisa plana) PADA TANAMAN KELAPA SAWIT - Luqiyarrohman; Aulia, Rahmawati (Agro Estate, 2024)
Oil palm is an important asset of Indonesian plantations. Problems in cultivation are mainly bagworm (Metisa plana) attacks that reduce growth by eating oil palm leaves and reducing yields. To overcome this problem, the application of bioinsecticides such as Bacillus thuringiensis (Bt) is a substitute for chemical pesticides. Bt produces toxic crystalline proteins that target the insect's gutreceptors, so it does not harm non-target organisms. The research was conducted in Teluk Panji IV Village, North Sumatra. The research design used a completely randomized design with five treatments and four replicates for seven days. The treatments were the use of Bt at concentrations of 0, 5, 10, 15, and 20 grams per liter. This study aims to assess the dose of Bt application as a sustainable pest management strategy in oil palm cultivation. The results showed that the treatment of Bt doses (0.5 g/L, 10 g/L, 15g/L, and 20 g/L had no significant effect on each observation variable. Symptoms of bagworm infestation included decreased appetite and movement within 24 hours after application, followed by discoloration and dark brown discharge between days 3 to 5,which eventually led to death and decay. Although the treatment results were not significant, the use of Bt bioinsecticide can still be used to control bagworm pests because some bagworms in this study died There were 51 caterpillars with the highest mortality at 20 g/l concentration.